Aerobic and anaerobic co-cultivation of Nannochloropsis oculata with oil palm empty fruit bunch for enhanced biomethane production and palm oil mill effluent treatment - Ahmad, A. (Taylor and Francis Inc., 2015)
This study explored co-cultivation of Nannochloropsis oculata microalgae with oil palm empty fruit bunch (OPEFB) for anaerobic biomethane production and palm oil mill effluent (POME) treatment. The highest specific biogas production rate (1.13â1.14Â m3Â kgâ1Â COD dâ1) and methane yield (4606â5018Â mL CH4 Lâ1 POMEÂ dâ1) were achievedÂ with co-cultivation of N. oculataÂ (2Â mL/mLÂ POME) and OPEFB (0.12Â g/mLÂ POME), as similarly predicted by response surface methodology for optimum conditions. Without microalgae and OPEFB co-cultivation, the biomethane yield was 1.3-fold lower, although the specific biogas production rate remained constant at 1.13â1.16Â m3Â kgâ1Â COD dâ1. Aerobic and anaerobic treatment of POME after 7Â d with microalgae achieved higher removal efficiency of COD (90â97), BOD (84â98) and TOC (65â80) as compared to without microalgae with COD (58â68), BOD (77â86) and TOC (58â68). Â© 2014 Balaban Desalination Publications. All rights reserved.